2010
DOI: 10.1136/bjo.2009.168864
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia reduces secretion of vascular endothelial growth factor by cultured retinal pigment epithelial cells

Abstract: Hypothermia decreases both VEGF secretion and cellular metabolism in ARPE-19 cells. Hypothermia also mitigates the hypoxia-induced increase in ARPE-19 cell VEGF secretion. These effects of hypothermia are potentially unique and cannot be obtained by other pharmacological agents that slow cellular metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 69 publications
1
14
0
1
Order By: Relevance
“…In one of these studies, it was reported that the thermal environment of the retina is important, and that choroidal circulation modulates the thermal environment of the macula [31]. Studies associating VEGF with intraocular temperature, which have found that VEGF secreted from the retinal pigment epithelium decreased in case of hypothermia, have also been published [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…In one of these studies, it was reported that the thermal environment of the retina is important, and that choroidal circulation modulates the thermal environment of the macula [31]. Studies associating VEGF with intraocular temperature, which have found that VEGF secreted from the retinal pigment epithelium decreased in case of hypothermia, have also been published [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Supporting these data, there are also some in vitro and ex vivo experiments showing that exposing isolated retinas or cultured retinal cells to cold temperatures results in reducing NMDA-mediated excitotoxicity [19], reducing secretion of vascular endothelial growth factor (VEGF) [20], and increasing survival against toxicants [21]. Hopefully, these promissing observations would be translated into clinical treatments soon.…”
Section: Introductionmentioning
confidence: 99%
“…Incubation of human vascular endothelial cells under “hypothermic” conditions (i.e., ≤34°C) reduces their capacity to form tubes in vitro (Coassin et al, 2010; Takeyama et al, 2015). Hypothermia also significantly reduces VEGF secretion and mRNA expression by retinal pigment epithelial cells (Coassin et al, 2010; Takeyama et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Second, angiogenesis is closely linked with muscle repair. Evidence from other tissue types suggests that hypothermia can alter the secretion of vascular endothelial growth factor (VEGF) (Coassin et al, 2010; Takeyama et al, 2015) and angiogenesis (Kuo et al, 2010; Kao et al, 2011). It remains unknown whether hypothermia exerts similar effects in skeletal muscle tissue.…”
Section: Introductionmentioning
confidence: 99%